Multiculturalism and Identity Construction in Zadie Smith’s White Teeth (2001) - Boudejema, Yasmin; Addala Amira; Bederina ,Ahlam Sarra (University of Ammar Theledji -Laghouat, 2020)
Postcolonial writers introduce an extract to the obstacles of living in in the sphere of Postcolonialism. More particularly, Zadie Smith‘s first novel White Teeth that was first published in the spring of 2000, whose primary emphasis is on multiculturalism and the identity construction of the first and the second generation of immigrants. White Teeth depicts the hindrances that faced people who attempt to coexist in culturally diversified communities. Smith portrays contemporary England through her novel and shows the alienation of the first generation of immigrants from the British society who are still connected to their roots and history. However, the second generation of immigrants, also known as the England-born generation, see themselves in an in-between position; neither do they belong to their home culture, identity, or the English one. They face many barriers in constructing their own identity and realizing their social status; they are too English in their homes, but they are strangers to English society. This research paper aims to present contemporary multicultural England through the lens of some theories and aspects of postcolonialism, which are applied in analyzing the novel like Homi K. Bhabha‘s concepts of culture and identity. The qualitative approach will serve to examine how the intersections of cultures influence identity construction, in addition to the interference of the analytical and descriptive method to extract the influences of one‘s roots and history on the construction of a whole generation‘s identity